Historical Sensibility in Tahira Iqbal's Novels Neli Bar and Graan - Taimoor khan, Muhammad Taimoor; Dr. Humaira Ishfaq (Zaban-o-Adab, 2024)
Tahira Iqbal is one of the most important writers of Urdu literature, who is a multi-faceted personality, and she is one of the most famous fictional writers and novelists of the present era. , social and political references are found that narrate moment by moment changing history and its impact on society. The post-Pakistan difficulties, migration events abroad in exchange for economic depression and the situation of the common citizen during different regimes have been mapped. In these novels, the effects of modernization and globalization on our society are also found. Thus, this research not only sheds light on the cultural and social movements embedded in Urdu literature, but also speaks to the historical, cultural and social consciousness of the writer Tahira Iqbal. There is evidence